ANALISIS PENGARUH AGLOMERASI, TENAGA KERJA, JUMLAH PENDUDUK, DAN MODAL TERHADAP PERTUMBUHAN EKONOMI KABUPATEN KENDAL - Ardyan Wahyu Sandhika; Mulyo Hendarto (Universitas Diponegoro, 2012)
ABSTRACT Economic growth is defined as an increase in the ability of an economy in producing goods and services. A high and sustainable growth is the main condition which indicates that economic development is running. Gross regional domestic product Kendal peaked at low enough with other districts in Central Java Province. This research aims to analyze the factors that can influence the growth of 19 subdistricts in Kendal, with the application of neo-classical growth model developed by Robert Sollow. Conduct analysis by Ordinary Least Square (OLS). Independent variable methods used namely : Agglomeration, Labor, Overcrowding, and the dependent variable is the economic growth. Research results showed the agglomeration with variable coefficient of Prob-sig 0,0000 and less than 5%, then have a positive influence on economic growth and significant Kendal Regency. Labor variable with coeficients 0,800532 and 0,4431 have a prob-sig positive influences and not significant, the number of resident variable showed negative influence with coefficient -10,93938 and significant to economic growth with prob-sig 0,0000 less than 5%. Lastly, variable capital has a positive influence with coefficient 1,199081 and significant with prob. 0,0024